2008
DOI: 10.1159/000160960
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia and Its Subtypes in an Elderly Urban Korean Population: Results from the Korean Longitudinal Study on Health and Aging (KLoSHA)

Abstract: Background/Aims: We estimated the prevalence of dementia and its major subtypes in an elderly urban Korean population. Methods: A study population of 1,118 Korean elders was randomly sampled from the residents aged 65 years or older living in Seongnam, Korea. Standardized face-to-face interviews, and neurological and physical examinations were conducted on 714 respondents. Dementia was diagnosed according to the DSM-IV diagnostic criteria, and its subtypes were determined according to the criteria of the NINCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 58 publications
4
67
1
1
Order By: Relevance
“…As regards the major dementia subtypes, the results confirmed what is being found by other studies: that AD is the most frequent subtype in older adults, followed by VD [35,36,37]. AD was diagnosed in 63.7% of the cases, a result similar to those obtained by other studies that have shown AD to affect more than 50% of cases of individuals aged 65 or more years [6,28], and more than 60% among still older age groups [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…As regards the major dementia subtypes, the results confirmed what is being found by other studies: that AD is the most frequent subtype in older adults, followed by VD [35,36,37]. AD was diagnosed in 63.7% of the cases, a result similar to those obtained by other studies that have shown AD to affect more than 50% of cases of individuals aged 65 or more years [6,28], and more than 60% among still older age groups [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Among countries in the Asia-Pacific region, the variation in dementia prevalence rates was consistent with the broad picture, as illustrated by recent publications of large studies [8,9,10,11,12,13,14,15,16,17,18,19,20] (table 1). Notwithstanding some differences in age among populations compared, there is a clear suggestion that dementia prevalence is higher in Japan and Korea, which are relatively higher income countries.…”
Section: Geographical Variations In Dementia Prevalence Ratessupporting
confidence: 83%
“…We tested the criterion validity of the FAB-K using AD as the gold standard, since AD is the most common cause of dementia [38,39] . Approximately 60% of AD patients manifest variable executive/frontal dysfunctions [4,17] , and thus AD may be the most common cause of dysexecutive syndrome in clinical settings.…”
Section: Discussionmentioning
confidence: 99%